Experiences of Patient-Led Chronic Pain Peer Support Groups After Pain Management Programs: A Qualitative Study. Issue 12 (28th June 2021) - Farr, Michelle; Brant, Heather; Patel, Rita; Linton, Myles-Jay; Ambler, Nicholas; Vyas, Sareeta; Wedge, Hannah; Watkins, Sue; Horwood, Jeremy
Abstract: Objective: A qualitative study of patients' experiences and the impacts of peer support groups that patients maintained after UK NHS group pain management programs (PMPs). Design: Long-term impacts of group PMPs remain unclear, with indications that positive effects can fade. We evaluated a model of continued peer support, co-produced by patients and clinicians, to maintain the therapeutic impact of PMP groups. A protocol was implemented that encouraged patients to continue to meet in their established PMP group for patient-led peer support (without clinical input) after PMPs finished. Peer support aimed to consolidate self-management, and advance social life recovery. We examined the impacts that groups had on attendees, and why some dropped out. Methods: Semi-structured interviews with 38 patients and 7 clinicians, analyzed thematically. Results: Friendship bonds and mutual understandings of effective ways of coping with pain encouraged participants to maintain recovery following PMPs. After PMP professional involvement has ended, these meetings enabled patients to develop greater agency from the shared sense of helping bring about new achievements or averting setbacks. Peer support extended the understanding of what is possible when living with pain. However, continuing meetings were not right for all. Reasons for not attending included lack of connection with peers. Conclusions: Co-produced peer support groups after PMPs can be a low-cost, effective social intervention, providing emotional, practical and social benefits, with improved self-management skills, stronger social connections and some reduced use of health services. Project resources for developing peer support meetings after PMPs are freely available online.